Designing Urban Learning Places at Secondary Schools - ashraf elmokadem; Hossam Samaty; Mariam Atout (Port Said Engineering Research Journal, 2019)
School environment is important for student’s development. Environmental psychology theories suggest that environmental context affects attitudes and social behavior. Research focuses on the relationship between the external physical environment of urban learning spaces at secondary schools and the student’s behavior in Egypt. Moreover, the research problem focus on neglecting of the physical area surrounding the schools and its lack of suitability for the different needs of adolescents. Accordingly, the results show that the relationships between the school's physical environment and the student's behavior. The design and planning of the school's external environment should push more attention to creating an enabling learning environment that can promote positive social behavior, especially in urban learning spaces at schools.